ONE OF APPROACHES TO MINIMIZE THE NUMBER OF VEHICLES FOR MORNING STUDENT´S HAULAGE TO SCHOOLS (Perner's Contacts, 2011)
Peak travel periods are characteristic attributes of urban passenger transport. Increased numer of vehicles has to be engaged in peak hours as a consequence of increased travel demand. The article presents one of methods to minimize the number of vehicles needed for a morning student´s haulage. A mathematical model for solving this problem is presented in this article too. Functionality of the model is demonstrated by example solved using software Xpress-IVE.
Keywords: optimization; linear programming; vehicles scheduling